Cardiac Manifestations of Coronavirus (COVID-19)-An Updated Review for Healthcare Professionals - Alrakkad, Abdullah Abdulkarim; Al-Hamzani , Abdulaziz Menwer; Alsalman, Laila Hassan Abdullah; Hospital, Muzahmiyah General; Alotaibi, Mohammed Abdulah; Alanazi, Fatimah Ahmed Hattab; Bakaralanzi, Eidh Khalaf; Al Salman, Laila Hassan; Somily, Sultan Mohammed; Ayyashi, Yasir Jubran Mousa; Alqahtani, Jamla Omar; Alomar, Khalid Abdualiziz; et al. (Journal of Ecohumanism, 2024)
Background: Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, primarily affects the respiratory system, but also presents significant cardiac manifestations. While acute respiratory symptoms are typical, COVID-19 is linked to numerous cardiovascular complications such as ischemic heart disease, arrhythmias, heart failure, and myocarditis. These complications, particularly in individuals with preexisting cardiovascular conditions, are associated with poorer outcomes. Aim: This review aims to comprehensively explore the cardiac manifestations of COVID-19, evaluate their pathophysiology, and assess current treatment strategies for managing these complications. Methods: This updated review consolidates findings from recent studies on the cardiovascular impact of COVID-19, drawing from clinical, epidemiological, and pathophysiological data. Literature sources were reviewed from various academic and clinical studies focusing on the prevalence, diagnosis, and management of cardiac issues associated with COVID-19. Results: COVID-19-related cardiac complications, including acute cardiac injury, myocarditis, arrhythmias, and heart failure, have been reported across multiple studies. The prevalence of cardiac injury among hospitalized COVID-19 patients ranges from 22% to 30%, with a notable increase in those over 60 years old. Acute coronary syndrome and arrhythmias are particularly common in older patients with preexisting cardiovascular risk factors. Post-mortem studies reveal myocardial necrosis, edema, and endothelial damage, suggesting a multifactorial pathophysiology involving inflammation, thrombosis, and viral invasion. Conclusion: COVID-19 presents a complex challenge for healthcare professionals due to its significant cardiovascular impact, particularly in patients with pre-existing heart conditions. Cardiac complications must be closely monitored, and appropriate management strategies are critical in improving patient outcomes. Future studies should focus on refining diagnostic methods and exploring long-term cardiac health in post-COVID-19 patients.